The hush [compact disc, unabridged] - Hart, John, 1965- (Macmillan Audio, 2018)
It's been ten years since the events that changed Johnny Merrimon's life. Since then, Johnny has fought to maintain his privacy. His only connection to normal life is his old friend, Jack. But Jack sees danger in the wild places Johnny calls home; he senses darkness and hunger, an intractable intent.